The miR-30 microRNA family targets smoothened to regulate hedgehog signalling in zebrafish early muscle development - Ketley, Ami; Warren, Anne; Holmes, Emily; Gering, Martin; Aboobaker, A. Aziz; Brook, J. David (Public Library of Science, 2013)
The importance of microRNAs in development is now widely accepted. However, identifying the specific targets of individual microRNAs and understanding their biological significance remains a major challenge. We have used the zebrafish model system to evaluate the expression and function of microRNAs potentially involved in muscle development and study their interaction with predicted target genes. We altered expression of the miR-30 microRNA family and generated phenotypes that mimicked misregulation of the Hedgehog pathway. Inhibition of the miR-30 family increases activity of the pathway, resulting in elevated ptc1 expression and increased numbers of superficial slow-muscle fibres. We show that the transmembrane receptor smoothened is a target of this microRNA family. Our results indicate that fine coordination of smoothened activity by the miR-30 family allows the correct specification and differentiation of distinct muscle cell types during zebrafish embryonic development.